PATH INTEGRAL AND OPERATOR APPROACH FOR THE PODOLSKY-SCHWINGER MODEL - Belvedere, L. V.; Natividade, C. P.; Galvao, CAP (Springer, 1992)
We study the role of the thachyonic excitation which emerges from the quantum electrodynamics in two dimensions with Podolsky term. The quantization is performed by using path integral framework and the operator approach.